Menumbuhkan Sikap Bangga Berbahasa Indonesia Sebagai Bahasa Nasional Dan Internasional - Nurlaela Az Zahra; Wulan Ambarwati (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2022)
Over the years, Indonesian has developed into the state language and national language, but many Indonesians cannot be proud of it. When they talk about Indonesia without really understanding it, the fact is clear. One of the reasons for this lack of pride is the implementation of the educational process by the government, the community, and the teaching staff. Although there are several rules regarding the use of the Indonesian language, the government has not taken serious action against public violations. people are more proud to use a foreign language than Indonesian, and young people today are less interested in learning it so they cannot create pride in their language, namely Indonesian.